The effect of alloying element in lead-free solders on intermetallics growth with enimag surface finish - Jaidi, Zolhafizi (2020)
Surface finish is coated layer plated on a bare copper board of printed circuit board (PCB). Among PCB surface finishes, Electroless Nickel/Immersion Gold (ENIG) finish is a top choice among electronic packaging manufacturer due to its excellent properties for PCB. However, the use of gold element in ENIG is very high cost and the black pad issue has not been resolved. Thus, by introducing an Electroless Nickel/Immersion Silver (ENIMAG) as alternative surface finish hopefully can reduce the cost and offer better properties. The aim of this study is to investigate the effect of alloying element in lead-free solders on interfacial reaction during reflow soldering between Sn-2.5Ag (SA25), Sn-2.5Ag-0.5Cu-1.0Bi (SACB25051), Sn2.0Ag-0.7Cu-3.0Bi (SACB20073) and Sn-3.4Ag-4.8Bi (SAB3448) with an ENIMAG surface finish. Solder balls with sizes of 500μm diameters were used. All samples were subjected to an isothermal aging process with four different aging times which are 250 hours, 500 hours, 1000 hours and 2000 hours at 150°C. The characteristics of intermetallic compound (IMC) were analyzed by using scanning electron microscopy (SEM), optical microscope (OM) and energy dispersive x-ray (EDX). The results revealed that there is one layer of (Cu,Ni)6Sn5 IMC was formed at the interface after reflow soldering and a new layer of (Cu,Ni)3Sn4 IMC has been found after isothermal aging take place. Subsequently, the grain size and thickness of IMC for SACB20073 is smaller and thinner compared to the SACB25051 followed by SAB3448 and SA25. This is due to the existence of Bi element which can reduce the grain size and the growth rate of IMC. The IMC thickness is proportional to the aging duration and IMC morphology for all solders are became thicker, larger and coarser after exposed to isothermal aging. Furthermore, the nanoindentation test had been conducted and ENIMAG was found reliable and suitable as protective layer for PCB. In addition, it is proved that there was electrical connection between solder ball and ENIMAG through conductivity test and the value of conductivity of SA25 is higher than SAB3448, SACB2551 and SACB20073.